2022
DOI: 10.1038/s41398-022-02260-x
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathic and autistic traits differentially influence the neural mechanisms of social cognition from communication signals

Abstract: Psychopathy is associated with severe deviations in social behavior and cognition. While previous research described such cognitive and neural alterations in the processing of rather specific social information from human expressions, some open questions remain concerning central and differential neurocognitive deficits underlying psychopathic behavior. Here we investigated three rather unexplored factors to explain these deficits, first, by assessing psychopathy subtypes in social cognition, second, by invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 101 publications
(154 reference statements)
0
3
0
Order By: Relevance
“…In terms of limitations of the included research, only two studies ( 67 , 74 ) differentiated between primary and secondary psychopathy and none considered the impact of adverse childhood experiences. In psychopathy research, children with CUTs showed strongest deficits in emotion recognition when there was no history of maltreatment, suggesting that this may be a feature of the primary variant only ( 108 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of limitations of the included research, only two studies ( 67 , 74 ) differentiated between primary and secondary psychopathy and none considered the impact of adverse childhood experiences. In psychopathy research, children with CUTs showed strongest deficits in emotion recognition when there was no history of maltreatment, suggesting that this may be a feature of the primary variant only ( 108 ).…”
Section: Discussionmentioning
confidence: 99%
“…Skjegstad et al. ( 74 ) reported deficits in both trait groups for socio-affective processing, but again these showed different areas of association; autistic traits were associated with deficits in dorsal auditory processing streams (used for communication context encoding), whilst psychopathic traits were associated with hypoactivity in socio-affective processing networks. This study was exploratory and lacked an a priori power calculation, but both studies suggested distinct neural mechanisms across these constructs.…”
Section: Autism and Psychopathy In Adultsmentioning
confidence: 99%
See 1 more Smart Citation